Reframing Fish Passage Prioritization for Human Nutrition Outcomes - Nicolette Duncan; Ana Horta; John Conallin; Tim Marsden; Abigail J. Lynch; Ivor Stuart (Environmental Management, 2025)
Water control infrastructure forms barriers that fragment river habitats, reducing aquatic biodiversity and the ecosystem services it provides. Irrigation infrastructure, for example, although implemented to support food production, highlights problematic trade-offs against wild food systems like inland fisheries which are a critical food resource for tens of millions of people, particularly in tropical countries. To reduce fragmentation at a broad range of barriers, fish passage technology is sometimes implemented to support migrating fish, aided by frameworks designed to prioritize barriers for remediation. This study critically evaluated 93 fish passage barrier prioritization frameworks globally to explore how they could strategically guide fish passage investments in tropical contexts and identify criteria relevant to delivering on nutrition security outcomes. Results showed prioritization frameworks were ill-equipped to support the broader human development goals that may drive fish passage investments in tropical countries, such as supporting human nutrition under United Nations Sustainable Development Goal (SDG) 2: Zero Hunger. Tropical contexts were underrepresented despite substantial recent fish passage investment, whereas temperate and conservation focused frameworks, particularly from North America, dominated. These findings prompt reflection on the inherent biases in fish passage barrier prioritization frameworks and criteria. Improving understanding of and collaboration with local partners to integrate SDG 2 into future prioritization frameworks could improve fish passage infrastructure and help support better nutrition and food production for communities.

Evaluation of a new practical low-cost method for prioritising the remediation of fish passage barriers in resource-deficient settings - Tim Marsden; Lee J. Baumgartner; Deanna Duffy; Ana Horta; Nathan Ning (Ecological Engineering, 2023)

Using fish swimming ability to refine criteria for fishway construction in Myanmar - John Conallin; Nyi Nyi Tun; Aye Myint Swe; Lee J. Baumgartner; Zau Lunn; Martin Mallen-Cooper; Tim Marsden; Nathan Ning; Wayne Robinson; Lalantha Senevirathna; Peter Thew (Fisheries Research, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Is There a Role for Human-Dominated Landscapes in the Long-Term Conservation Management of the Critically Endangered Kipunji (Rungwecebus kipunji)? - Claire E. Bracebridge; Tim R. B. Davenport; Vicky F. Mbofu; Stuart J. Marsden (International Journal of Primatology, 2013)